De Statua - Cellini, Benvenuto; Eliot, T. S. (Thomas Stearns), 1888-1965; Fuchs, Rudi H.; Rosso, Medardo; Van Abbemuseum, Eindhoven (Eindhoven : Van Abbemuseum Eindhoven, 1983)
Andre, Carl ; Baselitz, Georg ; Beuys, Joseph ; Chamberlain, John ; Fabro, Luciano ; Flanagan, Barry ; Immendorff, Jörg ; Long, Richard ; Lüpertz, Markus ; Nauman, Bruce ; Penck, A.R. ; Penone, Giuseppe ; Rückriem, Ulrich ; Visser, Carel
+ 1 dubbel
bibliog. P. 43-45
Engels
Nederlands
De Statua, Van Abbemuseum Eindhoven, May 8 until June 19, 1983
boek